2020
DOI: 10.3390/nu12020316
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Muscle Damage and Cardiac Stress During a Marathon Could be Associated with Dietary Intake During the Week Before the Race

Abstract: Adequate food intake is important prior to endurance running competitions to facilitate adequate exercise intensity. However, no investigations have examined whether dietary intake could prevent exercise-induced muscle damage (EIMD) and cardiac stress (EICS). Thus, this study’s objective was to determine the associations between EIMD, EICS and endurance athlete diets one week before a marathon race. Sixty-nine male runners participated in this study. Food intake during the week prior to the race was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 64 publications
2
17
2
Order By: Relevance
“…The same holds true for the dietary habits of the participants prior to our study. It has been found that regular consumption of specific food products is associated with differences in exercise-induced muscle damage and cardiac stress [45], which might have influenced cortisol response and perceived exhaustion. Next to this, it is recommendable to repeat the study in female athletes, as they are underreported in research.…”
Section: Discussionmentioning
confidence: 99%
“…The same holds true for the dietary habits of the participants prior to our study. It has been found that regular consumption of specific food products is associated with differences in exercise-induced muscle damage and cardiac stress [45], which might have influenced cortisol response and perceived exhaustion. Next to this, it is recommendable to repeat the study in female athletes, as they are underreported in research.…”
Section: Discussionmentioning
confidence: 99%
“…The athletes obtained a personalized diet for a 48-h period prior to T1 and marathon race day with 9 g CHO/kg BM/day, 1.5 g protein/kg BM/day and 0.5 g fat/kg BM/day to adjust their glycogen content. This diet comprised, among other foods, vegetables, olive oil and fish, although it did not contain any fatty meat or butter [ 41 ]. Moreover, runners had breakfast (2 g CHO/kg BM) at the ElikaEsport Health Center 3 h prior to commencement of the mountain marathon race.…”
Section: Methodsmentioning
confidence: 99%
“…Rhabdomyolysis (RM) is a clinical syndrome characterised by the breakdown of skeletal muscle bres and release of their contents into the circulation [1]. It can be caused by many reasons, such as trauma [2,3], heat exposure [4], marathons [5], drugs [6] and viruses (such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)) [7][8][9]. Myoglobin-induced acute kidney injury (AKI) is one of the most severe complications of RM [10].…”
Section: Introductionmentioning
confidence: 99%